(untitled) - Lind, Douglas A (New York, 2008)
19 chapters: using microsoft excel spreadsheets; Describing data: frequency distributions and graphic presentations; describing data: displaying and exploring dat ta;...
Keywords: Basic statistics -- Excel 2007 -- Business -- Economics; Thống kê cơ bản -- Excel 2007 -- Kinh doanh -- Kinh tế